Implementation of Server Up-Scaling to Improve the Performance and Reliability of the ZIS Information System - Azzahari, Muhammad; Safriadi, Safriadi; Putra, Arwin; Ridha, Risky; Rozaliana, Rozaliana (Politeknik Negeri Lhokseumawe, 2025)
The management of zakat, infaq, and shadaqah (ZIS) using information systems requires reliable server infrastructure to ensure system performance and service availability. The ZIS Information System experienced performance degradation and service instability due to increasing user access and system activities. This study aims to implement server up-scaling to improve the performance and reliability of the ZIS Information System. The research method employed is Research and Development (RD) using a prototyping approach. Server up-scaling was implemented by increasing server resource capacity, including memory and processor, without modifying the existing system architecture. System testing was conducted using black box testing to verify functional correctness, along with performance testing based on response time and system downtime before and after up-scaling. The results show that server up-scaling significantly reduces response time and eliminates system downtime during the testing period. Therefore, server up-scaling is proven to be an effective approach for improving the performance and reliability of web-based ZIS information systems.